Abusos de menores en la Iglesia: ¿Cómo hemos llegado hasta aquí? Breves apuntes sociológicos - Elzo Imaz, Javier (Razón y fe, 2019)
Given the magnitude of what we know about pedophilia among the Catholic clergy, I will dwell on two issues. First, the complex and slippery subject of contextualization, because only when one understands a reality (making it clear that understanding does not mean justifying), one is able to face it with intelligence and the capacity to overcome it. Secondly, I will present some points for reflection, which I consider to be central, in order to try to understand how the current situation has been reached. Although what is essential at this moment is to help the victims of abuses and the Church’s response to this situation, it also seems to me important, although secondary today, to analyze the published information on this reality, as well as the dimension of pedophilia of the clergy, in relation to pedophilia in society in general and in some more specific areas in particular, questions which I do not address in this article.
Keywords: pedophilia; clergy; contextualization; Catholic Church